Հայաստանի ազգային գրադարան-ուսումնական հաստատություններ փոխգործակցությունը պրակտիկայի կազմակերպման դիտանկյունից - Ղազինյան, Մհեր (Հայաստանի ազգային գրադարան)
The purpose of present article is to introduce the programme of internship of students from different academic institutions. Interns of Valery Brusov State University, Vardges Amazaspian State College of Echmiadzin, Armenian-Greek State College of Tourism, Service and Food Industry of Yerevan completed an internship at the National Library of Armenia. From the point of view of practice, the following issues are also important: strengthening cooperation between academic institutions and National Library of Armenia, continuity of the theory-knowledge-practical application chain, consideration of theoretical, practical, methodological foundations of educationlibrary relations, assessment, etc. The trainees got acquainted with the mission of the National Library of Armenia, the work of various departments and other related issues. They did their own assignments. We hope that the cooperation between the National Library of Armenia and academic institutions will be continuous.
Keywords: Հաղորդումներ; Հայաստանի ազգային գրադարան-ուսումնական հաստատություններ փոխգործակցություն